A 1, 8-naphthalimide-based fluorescent probe for selective and sensitive detection of peroxynitrite and its applications in living cell imaging. Issue 54 (7th July 2017) - Li, Xiulan; Hou, Jingli; Peng, Chao; Chen, Li; Liu, Wenbo; Liu, Yangping
Abstract : An "off–on" fluorescent probe for sensitive and selective detection of peroxynitrite was synthesized and showed good photostability and low cytotoxicity. Abstract : Peroxynitrite (ONOO − ) is an extremely reactive oxygen species which can damage a wide array of biomolecules in cells and eventually result in mitochondrial dysfunction and cell death. Detection and imaging of this species is of significant importance to understand its role in biological processes. However, current methods are mostly limited by low sensitivity and/or specificity. In this work, we designed and synthesized a new 1, 8-naphthalimide-based turn-on fluorescent probe NP for ONOO − in which the 1, 8-naphthalimide fluorophore was directly conjugated with a methyl(4-hydroxyphenyl)amino group. The reaction of NP with ONOO − led to the oxidative N -dearylation of the methyl(4-hydroxyphenyl)amino group and produced a highly fluorescent product NP-P. The probe NP exhibited high sensitivity for ONOO − with a detection limit of 11 nM and high specificity over other reactive species in phosphate buffer. Moreover, NP was used to specifically detect ONOO − generated in RAW264.7 murine macrophages upon stimulation by LPS and IFN-γ. Our present study sheds light on the design of new probes for ONOO − and the resulting probe NP has great potential in enabling selective and specific detection and imaging of ONOO − in different biological and chemical systems.